Papain as a Potential New Experimental Model of Non-histaminergic Itch - Giulia Erica Aliotta; Zeinab Saii; Jesper Elberling; Lars Arendt-Nielsen; Silvia Lo Vecchio (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)